2013
DOI: 10.1111/1471-0528.12357
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence during pregnancy: victim or perpetrator? Does it make a difference?

Abstract: Objectives To differentiate between forms of intimate partner violence (IPV) (victim only, perpetrator only, or participating in reciprocal violence) and examine risk profiles and pregnancy outcomes. Design Prospective Setting Washington, DC, July 2001 to October 2003 Sample 1044 high-risk African-American pregnant women who participated in a randomized controlled trial to address IPV, depression, smoking, and environmental tobacco smoke exposure. Methods Multivariable linear and logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 59 publications
2
23
2
1
Order By: Relevance
“…In another study, now of the type controlled clinical trial conducted with high-risk pregnant women in Washington, USA, it was observed that battered women were about 2.5 times more likely to have a child with LBW, an increase of approximately six-fold in the infants birth of very low birth weight (<1,500 g). 24 These findings corroborate with other studies listed in this review. 9,11,13,14,20,24,28,29 On the other hand, against these results, three studies did not find an association between intimate partner violence and low birth weight (p>0.05).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In another study, now of the type controlled clinical trial conducted with high-risk pregnant women in Washington, USA, it was observed that battered women were about 2.5 times more likely to have a child with LBW, an increase of approximately six-fold in the infants birth of very low birth weight (<1,500 g). 24 These findings corroborate with other studies listed in this review. 9,11,13,14,20,24,28,29 On the other hand, against these results, three studies did not find an association between intimate partner violence and low birth weight (p>0.05).…”
Section: Resultssupporting
confidence: 92%
“…24 These findings corroborate with other studies listed in this review. 9,11,13,14,20,24,28,29 On the other hand, against these results, three studies did not find an association between intimate partner violence and low birth weight (p>0.05). 10,16,30 Another finding in this review was the studies that associated violence with small to gestational age (SGA).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Surprisingly, couples with a male IPV victim only were the most prevalent group experiencing IPV, followed by couples with mutual IPV, and finally couples with a female IPV victim only. A randomized controlled trial delivering a behavioral intervention with a similar study population (urban minority women in prenatal care) found that while male victimization was more common than female victimization, mutual IPV was most prevalent during pregnancy (Shneyderman & Kiely, 2013). That study included adults and thus more cohabitating couples; mutual violence is more common if cohabitating (Cui, Ueno, Gordon, & Fincham, 2013).…”
Section: Discussionmentioning
confidence: 99%